The improtance of the sphincterotomy in the diagnosis of periampullary carcinoma: analysis of 664 patients who underwent ERCP - Yusuf BAYRAKTAR,; Ahmet ÖZGENÇ,; Arif ÖZDEMİR,; Gürol ÖKSÜZOĞLU,; Serap ARSLAN,; Teoman COŞKUN,; Bedri UZUNALİMOĞLU, (Turkish Journal of Gastroenterology, 2019)
-